2021
DOI: 10.1016/j.tranon.2021.101188
|View full text |Cite
|
Sign up to set email alerts
|

CT-based radiomics model with machine learning for predicting primary treatment failure in diffuse large B-cell Lymphoma

Abstract: Highlights CT-based radiomics with machine learning classifier is able to accurately predict primary refractory Diffuse Large B Cell Lymphomas (DLBCL). The radiomics model exhibits a better discrimination for refractory DLBCL identification compared to available standard clinical criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Nine studies applied ML to prognostication or predicting responses to therapy in patients with hematological malignancies ( Table 3 ): (i) predicting outcomes (overall survival or progression-free survival) in patients with extranodal NK/T-cell lymphoma, nasal type ( 69 ), multiple myeloma ( 70 , 75 ), DLBCL ( 71 ), and mantle cell lymphoma ( 73 ) or (ii) predicting responses to therapy in patients with DLBCL ( 68 , 76 ) and HL ( 74 ). One study aimed to identify high-risk cytogenetic (HRC) multiple myeloma patients by applying ML to MRI images ( 72 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies applied ML to prognostication or predicting responses to therapy in patients with hematological malignancies ( Table 3 ): (i) predicting outcomes (overall survival or progression-free survival) in patients with extranodal NK/T-cell lymphoma, nasal type ( 69 ), multiple myeloma ( 70 , 75 ), DLBCL ( 71 ), and mantle cell lymphoma ( 73 ) or (ii) predicting responses to therapy in patients with DLBCL ( 68 , 76 ) and HL ( 74 ). One study aimed to identify high-risk cytogenetic (HRC) multiple myeloma patients by applying ML to MRI images ( 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several different ML approaches were applied including a logistic regression classifier ( 68 , 72 ), random survival forests (RSFs ( 70 );), weakly supervised deep learning ( 69 ), ANN/CNNs ( 71 , 73 ), SVM ( 72 , 74 ), RF ( 72 , 75 , 76 ), DT ( 72 ), K-NN ( 72 ), and XGBoost ( 72 ). The models used a range of features including not only automatically extracted radiomic features but also clinicopathological variables in two studies ( 70 , 75 ), laboratory variables in one study ( 73 ), and two additional radiological features (nodal site and subjective necrosis) in one study ( 76 ). The models were validated by splitting the data or cross-validation, and no study tested the models on independent validation sets.…”
Section: Resultsmentioning
confidence: 99%
“…One report of nodal texture analysis in pediatric patients found a sensitivity in the range of 82.4–88.8% and a specificity in the range of 72.4–86% for detecting malignant lymph nodes 48 . Although there have been studies using radiomics or texture analysis for evaluation of neoplastic cervical lymph nodes in adults 33 , 47 , 49 , 51 , 53 , 58 , 59 , to our knowledge, our study is the first to assess radiomic features of NTM lymphadenitis. In addition, our analysis includes comparisons with pyogenic lymphadenitis, reactive and proliferative lymphadenopathy with a much larger sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Recently more publications discussing the utility of radiomics and machine learning for the evaluation of lymph nodes have demonstrated the utility of such approaches 33 , 45 – 57 . Lymph node radiomic features have been suggested to be highly predictive of malignant versus benign etiology 33 , 45 , 46 , 48 , 50 , 54 , 58 . One study carried out in the pediatric population reported a sensitivity of up to 82.4% and a specificity of 86.2% 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Schöder et al [11] utilized 18 FDG-PET scans at baseline, interim, and end of treatment (EoT) to identify biomarkers of response that are predictive of remission and survival. Recently, Santiago et al [12] built a CT-based radiomics approach that utilizes random forest (RF) machine learning for predicting refractory DLBCL. Senjo et al [13] measured metabolic heterogeneity using 18 FDG-PET/CT to predict a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%